INCREASING 24 HOUR MOBILITY IN OLDER MEDICAL PATIENTS: THE WALK-COPENHAGEN PROJECT. (11th November 2018) - Pedersen, M M; Kirk, J W; Petersen, J; Bandholm, T Q; Tjørnhøj-Thomsen, T; Nilsen, P; Andersen, O
Abstract: Low mobility in hospitalized patients can have serious health consequences. During hospitalization older medical patients spend most time lying in bed and numerous barriers toward mobility exist. Therefore, interventions that consider multiple determinants of older patients' mobility are warranted. The WALK-Cph project aims to increase 24-hour mobility in older medical patients during and after hospitalization. In six medical wards, we performed observations focusing on mobility. In a thematic analysis of data, five themes emerged: materialities, professional roles, encouraging moments, patients' and relatives' influence on mobility, and organization's and management's influence on mobility. "Professional roles" influenced all themes showing that health professionals follow different cultural models that create contradictions and boundaries and make it unclear who is responsible for the older patients' mobility. Based on these results, in subsequent workshops with key stakeholders (patients, relatives, researchers and health professionals) we developed an intervention to be tested in a randomized controlled trial.